2004
DOI: 10.1093/brain/awh154
|View full text |Cite
|
Sign up to set email alerts
|

Neurobiology of perceptual and motor timing in children with spina bifida in relation to cerebellar volume

Abstract: The cerebellum is important for perceptual and motor timing in the mature brain, but the timing function of the cerebellum in the immature brain is less well understood. We investigated timing in children with spina bifida meningomyelocele (SB), a neural tube defect that involves cerebellar dysgenesis, and in age-matched controls. Specifically, we studied perceptual timing (judgements of 400 ms duration) and motor timing (isochronous motor tapping); measured cerebellar volumes; and related perceptual and motor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
86
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 73 publications
(93 citation statements)
references
References 49 publications
4
86
0
2
Order By: Relevance
“…The number of valid tapping trials was positively correlated with anterior and inferior-posterior cerebellar volumes in the children with SBM. Even though perceptual and motor timing are different and controlled by separate structures, these two components are related to each other as evidenced by a fair level of correlation [33]. This may indicate that children with SBM have a central timing impairment.…”
Section: Martin S Austin Publishing Groupmentioning
confidence: 98%
See 1 more Smart Citation
“…The number of valid tapping trials was positively correlated with anterior and inferior-posterior cerebellar volumes in the children with SBM. Even though perceptual and motor timing are different and controlled by separate structures, these two components are related to each other as evidenced by a fair level of correlation [33]. This may indicate that children with SBM have a central timing impairment.…”
Section: Martin S Austin Publishing Groupmentioning
confidence: 98%
“…Researchers compared perceptual timing and motor timing in children with and without SBM [33]. Children with SBM had significantly more difficulty than age-matched controls on judging the duration of a timing task of 400ms duration.…”
Section: Timingmentioning
confidence: 99%
“…One study reported smaller cerebellar volumes in 52 children with SB compared with 16 age-matched controls using volumetric analysis on MRI [41] . The study also reported that the cerebellar gray and white matter volumes were both reduced, and the reduction was greater in children with high spinal lesion levels than in children with low spinal lesion levels.…”
Section: The Dysmorphology Of Chiari Type II Malformationmentioning
confidence: 99%
“…Thus, positioning anatomical markers across different scans for the purpose of averaging them is also difficult. Volumetric brain analysis using MRI in CII has been performed in one study [41] . It showed smaller cerebellar volumes in children with CII in comparison to age-matched controls [41] .…”
Section: Quantifying the Cerebellum Non-invasivelymentioning
confidence: 99%
“…The T2-weighted scan was then clustered to extract cerebrospinal fluid (CSF) vol- Verb generation in children with spina bifida 183 umes, and the latter was used to adjust the white and gray matter volume measures obtained from the T1-weighted scan. The quantitative segmentation procedure is described in Dennis et al (2004) and Fletcher et al (2005) and in Appendix A.…”
Section: Image Acquisitionmentioning
confidence: 99%